Ultra-intensity patriarchy: care and gender violence on the Paraná Tri-Border Area - Guizardi, Menara (Springer, 2021)
This book analyzes the experiences of women living and working across the busiest and most transited frontier in South America, the Parana Tri-Border Area (TBA), between Argentina, Brazil, and Paraguay. From a feminist approach, it shows how, in these territories, the gender violence is intensified, configuring an expression of ultra-intensity patriarchy. Based on ethnographic fieldwork conducted for two years along with Paraguayan women living and working between Ciudad del Este (Paraguay), and Foz de Iguazu (Brazil), the authors analyze, on the one hand, the intricate connection between gender violence and ethnicity on these borders; and, on the other hand, the persistence of a female care that appears to offer a fundamental tool of resistance, of vital female drive. The work is divided into three parts. The first is intended to read like a trip to this complex and fascinating corner of South America through a visual and ethnohistoric journey of the region, as well as a theoretical debate that defines gender violence and its particular condensation on border territories. The second part explores the womens stories in-depth and follow the narrative thread of their biographies, rebuilding their experiences from their families of origin to their productive insertion on the TBA. Finally, the third part takes an in-depth look at the complex links between the social reproduction obligations that fall on women, and the gender violence on the TBA, stressing how they develop strategies to change their life conditions by establishing transborder circuits of care. Ultra-Intensity Patriarchy: Care and Gender Violence on the Parana Tri-Border Area will be a valuable tool for researchers from different disciplines, such as anthropology, sociology, population studies and gender studies, interested in the growing field of studies of feminism, borders, and migration from an intersectional perspective